2023
DOI: 10.3389/fnut.2023.1114919
|View full text |Cite
|
Sign up to set email alerts
|

Culturally-tailored cookbook for promoting positive dietary change among hypertensive Filipino Americans: a pilot study

Abstract: IntroductionAmong all Asian American subgroups, Filipino-Americans have consistently been shown to have the highest rates of hypertension, raising risks of heart attack and stroke. Despite this alarming fact, little has been done to investigate culturally-sensitive interventions to control hypertension rates in this vulnerable population. To address the lack of culturally-relevant lifestyle options for blood pressure management currently available to the Filipino community, this exploratory pilot study used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Incorporating culture into nutritional counseling may incite greater adherence to dietary changes ( 37 ) and, consequently, promote better health. For example, a recent study showed that a cookbook tailored to a Filipino-American population may potentially motivate individuals to make healthier dietary choices ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating culture into nutritional counseling may incite greater adherence to dietary changes ( 37 ) and, consequently, promote better health. For example, a recent study showed that a cookbook tailored to a Filipino-American population may potentially motivate individuals to make healthier dietary choices ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the incorporation of culturally relevant foods is paramount when formulating dietary recommendations, with particular attention paid to the varied culinary customs found in Indonesia. It is recommended that dietary guidance incorporates cuisine that is familiar to diverse ethnic groups while also highlighting methods of preparing such food in a manner that promotes improved health outcomes (Forouhi, 2023;Sijangga et al, 2023). Rather than proposing a total adoption of novel or atypical food items amongst specific communities, the alternative approach could entail disseminating healthier preparation techniques for indigenous culinary choices (Amjad et al, 2023).…”
Section: Calling For Dmt2 Early Prevention Campaigns Through Multicul...mentioning
confidence: 99%